A framework for analysing the role of innovation policy in regional innovation system development. (2017) - Cai, Yuzhuo; Pugh, Rhiannon; Liu, Cui
This paper develops a framework for analysing the role of innovation policy in regional innovation system (RIS) development. It specifically focuses on the influence of policy on a set of enabling conditions for RIS that have not been taken fully into account in previous innovation policy studies. Drawing on relevant literature on innovation systems, such as innovation policy, triple helix and policy mix etc., the enabling conditions for RIS development identified include both tangible and intangible dimensions of regional contexts, hinging around a range of wider institutional backdrops. The framework proposed provides an effective analytical tool for innovation policy evaluation and for designing innovation policies.